Excretion of the drug glutaron - a new derivative of glutamic acid - L. A. Smirnova; E. A. Suchkov; A. F. Ryabukha; K. A. Kuznetsov; I. N. Tyurenkov; V. N. Perfilova (LLC "Publisher OKI", 2014)
In the study of excretion of the drug was found that glutaron determined in urine for at least 72 hours of the study. Renal clearance is 123 ml/hour, extrarenal - 34.84 ml/hour by intravenous route of administration. Superiority over extrarenal and renal clearance correlates with earlier data on the distribution of glutaron in organs and tissues. The drug was determined in the organs responsible for elimination (liver, kidneys and lungs) at high concentrations.